Praktik Prinsip-prinsip CP dalam Konteks EFL Perguruan Tinggi: Manfaat dan Tantangan - Yulianto, Slamet Wahyudi; Musthafa, Bachrudin; Gustine, Gin Gin (ELTIN Journal, 2024)
There is a lack of study focusing on the payoffs and pitfalls of integrating CP principles in EFL classrooms especially in the Indonesian higher education context. This case study research was performed to unearth the benefits and challenges of integrating the four CP principles consisting of dialogue, problem-posing, praxis, and conscientization in the tertiary education EFL context. The two EFL lecturers teaching in different higher education institutions Subang and Bandung, West Java Province were selected as the participants of this study. The data were collected using interview guideline and classroom observation sheet. The obtained data were then analyzed through transcribing, coding, categorizing, interpreting, comparing, and concluding. The result showed that there are two benefits and two challenges perceived by the participants. While the two benefits are improving students’ English proficiency and increasing their social awareness, the two challenges are students’ unwillingness to participate during the classroom discussions and predetermined curriculum. It is recommended for policy makers to promote the integration of CP in the EFL classrooms especially in the higher education institutions and for further researchers to conduct the identical study focusing on how the EFL educators practicing CP principles overcome challenges they face.